Analisis Implementasi Blockchain dalam Optimalisasi Pengelolaan Green Bond PT Sarana Multi Infrastruktur (PT SMI) di Indonesia - Thohira, Rasyiqa Annisa; Priatnasari, Saskia Febryanti; Winias, Putih Tri (MDP Student Conference, 2025)
PT Sarana Multi Infrastruktur (PT SMI) issued Indonesia’s first green bond in 2018 to support environmentally friendly infrastructure projects, such as renewable energy and sustainable transportation. However, a lack of transparency and effectiveness in fund management led to high operational costs and financial risks. This study explored the potential of blockchain technology as an innovation in PT SMI’s green bond issuance to address these issues. Using a literature review and exploratory approach, the research found that blockchain can significantly enhance transparency, accountability, and efficiency in fund management. Nevertheless, challenges such as limited technological infrastructure, low market awareness, and unclear regulations hinder its adoption. To enable implementation, responsive regulations and clear guidelines for issuing and managing blockchain-based green bonds are essential. This study aims to contribute to the development of efficient, transparent, and sustainable financial management in Indonesia through the integration of blockchain technology in green bond practices.